2003
DOI: 10.1136/heart.89.7.767
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in coronary artery bypass graft (CABG) trials: a systematic review and analysis

Abstract: Objectives: To quantify the incidence of major adverse events (AEs) occurring in hospital or within 30 days after surgery in patients undergoing coronary artery bypass graft (CABG) surgery and to identify risk factors for these AEs. Methods: Systematic review and analysis of studies published in English since 1990. Studies of isolated standard CABG reporting postoperative incidence of myocardial infarction (MI), stroke, gastrointestinal bleeding, renal failure, or death in hospital or within 30 days were eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
92
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 7 publications
8
92
1
6
Order By: Relevance
“…In a meta-analysis, Nalysnyk et al 22 observed a higher prevalence of men, lower rates of ventricular dysfunction, diabetes, and hypertension than in our study. 22 In Iran, Karimi et al 13 , from the Thoracic Surgery Society in the United States, reported on the correlation between volume and mortality of CABG: when the number of surgeries per hospital was lower than 100 procedures/year, the mortality rate was 5.0%, whereas when the number was higher, mortality was 3.2%. 24 In Brazil, from 1996 to 1998, by reviewing AIHs, Noronha et al 25 observed a CABG mortality rate of 7.2%.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In a meta-analysis, Nalysnyk et al 22 observed a higher prevalence of men, lower rates of ventricular dysfunction, diabetes, and hypertension than in our study. 22 In Iran, Karimi et al 13 , from the Thoracic Surgery Society in the United States, reported on the correlation between volume and mortality of CABG: when the number of surgeries per hospital was lower than 100 procedures/year, the mortality rate was 5.0%, whereas when the number was higher, mortality was 3.2%. 24 In Brazil, from 1996 to 1998, by reviewing AIHs, Noronha et al 25 observed a CABG mortality rate of 7.2%.…”
Section: Discussioncontrasting
confidence: 47%
“…It is important, however, that mortality rates observed in random clinical trials are generally lower than those observed in clinical practice. Therefore, in a meta-analysis on CABG adverse events conducted from 1990 to 2001, mortality rates, both in-hospital and up to 30 days after surgery, were 1.7% and 2.1%, respectively 22 . One study conducted with 51,353 patients who had undergone CABG from 1999 and 2002 in 69 US hospitals, revealed an in-hospital mortality rate of 2.63%, representing approximately 7% of all CABG surgeries performed in that country 11 .…”
Section: Discussionmentioning
confidence: 99%
“…And equal number of case found in wound infection in each group. These above findings were consistent with studies conducted by Ascione et al and Lslamoglu et al [14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 83%
“…In this specific cohort, the incidence of ARDS ranges from 0.4% to 20% (4-10) with high variability attributable to differences in design methodology of the studies, study populations and different ARDS definitions. Taking into account the fact that worldwide >800,000 patients per year undergo coronary artery bypass grafting (CABG) surgery and approximately 150,000 patients undergo valve surgery (11,12), ARDS undoubtedly represents a significant concern with profound economic implications.…”
Section: Introductionmentioning
confidence: 99%